Taxonomy for citizen actions on public health and climate change: a proposal - Lidice Álvarez-Miño; Robinson Taboada Montoya (Universidade de São Paulo, 2022)
ABSTRACT Facing complex issues such as climate change and its effects on public health require the participation of various actors. The research tool citizen science is one way for people to get involved. Through it, citizens collaborate with scientists to find solutions to problems in their territories. From a participatory work with citizens, we designed a taxonomy proposal, which can facilitate citizen and community action in suggesting research ideas. We expect stakeholders to use it to systematically classify and code initial questions and answers on public health and climate change issues. The development of this taxonomy integrates the global agenda of Sustainable Development Goals (SDG) in such a way that citizens not only help their communities but also, the direct fulfillment of SDGs such as Climate Action (SDG 13), indirectly impacting other SDGs - given their interdependent nature (SDG 3, SDG 5, SDG 6, SDG 7, SDG 11, SDG 12). The systematic classification and coding of citizens' contributions worldwide will contribute to the large-scale organized collection of information to be analyzed in proposing better responses to reduce the impacts of climate change on health.